Reproductive Performance of Kacang Goats in Closed Population Areas of Sidoarjo Regency, East Java, Indonesia - Fitria Ella Wardani; Desinta Wulandari; Inggita Leli Murtika; Ahmad Furqon; Wike Andre Septian; Tri Eko Susilorini; Suyadi Suyadi (ANIMAL PRODUCTION, 2022)
The objective of this study was to determine the reproductive performance of Kacang goats in a closed population area of Oro-Oro Farm located in Sawohan Village, Buduran Subdistrict, Sidoarjo Regency. We used 146 Kacang goat with a range of parity from 1 to > 7. Data analysis was carried out using the ANOVA test, Least Significant Difference (LSD) test, coefficient of variation test and descriptive test to measure litter size, pre-weaning mortality, kidding interval (KI), days open (DO) and Kacang goat reproduction index. The results showed that the highest litter size was 1.69 ± 0.63 at parity 6, the lowest pre-weaning mortality at parity > 7 was 11.76%, the shortest kidding interval and days open was at parity 4 for 7.35 ± 1.22 and 2.35 ± 1.22 months, respectively. The best Kacang goat reproduction index was 2.22 at parity 6 with coefficient of variation of 38.06%, 41.08% and 13.36% for litter size (LS), days open (DO), kidding interval (KI). Conclusively, there was a diverse reproductive performance of Kacang goats in the closed population area of Oro-Oro Farm located in Sawohan Village, Buduran Subdistrict, Sidoarjo Regency based on parity 1 to > 7, in which the higher the parity, the higher the reproductive performance. However, parity 5 onwards saw a declining reproductive performance due to weakened livestock conditions.